The Effect of Inquiry Learning Model on Mathematics Student Learning Outcomes Class IV State Elementary School 040544 Dolat Rayat - Tarigan, Adelina Theresia; Sinaga, Reflina; Simarmata, Ester J; Lumban Gaol, Rumiris; Juliana, Juliana (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
The purpose of this study is to ascertain how the inquiry learning paradigm affects students' learning outcomes in math class IV SD Negeri 040544 Dolat Rayat 2022/2023 Academic Year. The experimental technique was used in this study, and there were 195 students in grades I through VI at SD Negeri 040544 Dolat Rayat who made up the study population. Using a purposive sample, 31 pupils from class IV make up the sample. According to the study's findings, the average of 86.19 and a correlation test score of 0.855 place the student learning outcomes employing the inquiry model in the very good category. If rcount 0.855 is greater than rtable 0.355, then the hypothesis is accepted. As a result, the inquiry learning methodology has a significant impact on students' learning outcomes in math class IV SD Negeri 040544 Dolat Rayat. According to the findings of the T-test study, where tcount ttable is 8.861 2.045, Ha is deemed to be acceptable. This demonstrates that the application of the inquiry learning paradigm had a considerable favorable impact on student learning outcomes in math class IV SD Negeri 040544 Dolat Rayat in the 2022–2023 academic year.